2014
DOI: 10.1007/s00227-014-2463-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid changes in growth, condition, size and age of small pelagic fish in the Mediterranean

Abstract: Since 2007, the ecosystem of the Gulf of Lions has shifted to a different regime, characterised by a low anchovy (Engraulis encrasicolus) and sardine (Sardina pilchardus) biomass and a remarkably high sprat (Sprattus sprattus) biomass. Surprisingly, the abundance and recruitment of anchovy and sardine remained high. To understand which processes (bottom-up or top-down control, etc.) could have caused this shift, we studied the changes in body condition, growth and size and age of anchovy, sardine and sprat ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
117
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 33 publications
16
117
2
2
Order By: Relevance
“…( GFCM 2014GFCM , 2015, which confirm the MEDIAS survey data as an excellent benchmark. Moreover, a similar anchovy demographic structure for the same time period was found in the adjacent GSAs, GSA07, Gulf of Lions (Van Beveren et al 2014) and GSA03, southern Alboran Sea (Bacha et al 2010, 2014, Jemaa et al 2015. Other studies carried out in earlier years in the Mediterranean Sea reported a life expectancy of 3 to 4 years (Basilone et al 2004, Van Beveren et al 2014 and 5 years in the Bay of Biscay (Uriarte et al 1996), but all concluded that only a minor fraction belongs to these oldest age classes.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…( GFCM 2014GFCM , 2015, which confirm the MEDIAS survey data as an excellent benchmark. Moreover, a similar anchovy demographic structure for the same time period was found in the adjacent GSAs, GSA07, Gulf of Lions (Van Beveren et al 2014) and GSA03, southern Alboran Sea (Bacha et al 2010, 2014, Jemaa et al 2015. Other studies carried out in earlier years in the Mediterranean Sea reported a life expectancy of 3 to 4 years (Basilone et al 2004, Van Beveren et al 2014 and 5 years in the Bay of Biscay (Uriarte et al 1996), but all concluded that only a minor fraction belongs to these oldest age classes.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, a similar anchovy demographic structure for the same time period was found in the adjacent GSAs, GSA07, Gulf of Lions (Van Beveren et al 2014) and GSA03, southern Alboran Sea (Bacha et al 2010, 2014, Jemaa et al 2015. Other studies carried out in earlier years in the Mediterranean Sea reported a life expectancy of 3 to 4 years (Basilone et al 2004, Van Beveren et al 2014 and 5 years in the Bay of Biscay (Uriarte et al 1996), but all concluded that only a minor fraction belongs to these oldest age classes. Small pelagic fish are essential elements of marine ecosystems due to their significant biomass at intermediate levels of the food web, playing a considerable role in connecting the lower and upper trophic levels (Cury et al 2000).…”
Section: Discussionsupporting
confidence: 70%
“…All the pelagic fish make up 40% to 80% of hake diet in the GoL, indicating their key trophic role. Since the late 2000s, the pelagic ecosystem of the GoL has shifted to a different regime, characterized by a low biomass of anchovy and sardine related to a slowdown in growth and a bad body condition (Van Beveren et al 2014, Brosset et al 2015. Therefore, the population fluctuations and the general "state of health" of these two species may adversely affect the diet, body condition and reproduction of their predators, and consequently reinforce the decline of hake, a species that is already severely overexploited (Jadaud et al 2014).…”
Section: Stock Status Considerations With Regard To Dietmentioning
confidence: 99%
“…Total length (TL), fork length (FL) and standard length (SL) is usually utilized in different types of studies such as describing fish growth parameters and systematic studies (Arslan et al, 2004;Ma et al, 2010;Jia & Chen, 2011;Yılmaz & Polat, 2011;Yılmaz et al, 2012;Mohaddasi et al, 2013;Motamedi et al, 2014;Saylar & Benzer, 2014;Van Beveren et al, 2014;Hedayati et al, 2016;Turan et al, 2017). Therefore, length-length transformations in fish are useful for comparative studies using different length measures (Yılmaz et al, 2010;Tsagarakis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%